BIBLIOMETRIC ANALYSIS OF WORLDWIDE RESEARCH TRENDS ON RICE (Plant Bulletin, 2025)
Rice is the world's second most significant and extensively farmed grain crop and serves as the nutritional foundation of humanity. Thus, this agricultural plant is critical for world food security. A bibliometric study of rice-related scientific publications and patents using several databases was carried out. The number of documents produced each year, the subject categories, publishing journals, document types, and languages were all metricated. The primary keywords used in research articles on this crop were also examined globally and organized into subject categories. Distinct papers were analyzed independently while searching for terms relating to genetics and transgenic rice. A comparison of rice data revealed several noteworthy differences, the causes for which are explained further. The total number of documents with the term “rice” in 11 databases and over 1980-2023 is 8,009,800. There are 25 different languages in which documents are published; the biggest share belongs to the English language in Springerlink data. China ranks first in the number of publications on rice. The expanding amount of papers and patents indicates a continued interest and investment in improving rice-related knowledge and applications, offering valuable insights that contribute to further improvements in rice crop production.
Keywords: rice; grain crop; articles; genetics; transgenic rice; bibliometric